Considerations on sustainable development in the family economy of Espírito Santo - Canal, Mauro Henrique Massucatti; Santos, Bárbara Morais dos; Tosta, Marielce de Cassia Ribeiro (Brazilian Journal of Production Engineering, 2021)
Family farming differs from the model of an agricultural company, having as its main objective to initially meet the basic needs of the family, seeking to balance the use of natural resources and actively acting in the process of transition to sustainable agriculture. The use of pesticides is an important factor in achieving higher levels of productivity. However, this use has been occurring in an indiscriminate way, where most of the time there is no knowledge of the damage to health and the environment that these products can cause. The present work is a bibliometric analysis involving family farming on sustainability and sustainable development, as well as verifying the relationship with the income factor and the level of education, and also from the 2017 Agricultural Census data. to observe the main practices that promote or not the sustainability of the families. It is therefore concluded that: the use of chemicals in crops is lower as the level of education increases; the indiscriminate use of pesticides together with the lack of information causes serious environmental and health problems for the population.
Keywords: Family farming; Pesticide; Education level; Espírito Santo.; Family farming; Pesticide; Education level; Espírito Santo.